Risk Factors for Invasive Cervical Cancer among Distinct Populations in Low Resource Countries - Sania Ishtiaq Ratyal, Shaista Mukhtar, Maniba Habib, Ayesha Fatima, Izza Arshad, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Cervical carcinoma is the commonly known leading malignancy that has the highest prevalence in the developing countries. It shares second rank in the world of cancer. The 80% of the cases of the cervical cancer in the developing countries are reported. It is reported that the one woman die from this cancer after every two minutes. Objective: To identify the risk factors associated with the cervical carcinoma (CC). The role of human papillomavirus (HPV) in aetiology of cervical carcinoma was also evaluated. Study design: It is a hospital based case-control study. Material and Methods: The total 226 ICC cases were included in the study and 234 female were kept in control group. The study was conducted at the Divisional Headquarter Teaching Hospital of Mirpur AJK from May 2020 to May 2022. PCR was used for the evaluation of the HPV DNA in cervical cells. Multiple logistic models were used to compute the 95% confidence intervals CIs and odd ratios ORs. The all control women except one has the HPV infection. Results: The all control women except one has the HPV infection. The HPV of 23 different types associated with the risk of ICC. The HPV 16 was present in most of the patients either belong to case or control group followed by the HPV 18 and 33. HPV 18 has stronger association with ICC. The odd ratio of the single infection was higher than the multiple infections. Other factors such like early menopause, high parity and husband extramarital sexual affairs are also associated with the ICC. Conclusion: The HPV level is considered significant for the cervical carcinoma because of the lack of knowledge about other factors. A number of factors like socio-economic pressure, poor hygiene, menopause, education, and the sexual life of the husband of the patient play a major role in the carcinoma. Keywords: Cervical cell carcinoma, risk factors, human papillomavirus (HPV), squamous cell carcinoma, adenocarcinoma.